Lecturer Availability Tracking System (LATS) / Fadli Othman - Othman, Fadli (Faculty of Information Technology and Quantitative Science, 2006)
As a student, we realize that it is important to have a good relationship with our lecturer. But there are some students who find it hard for them to meet with their lecturer especially at the lecturer’s room. By calling or sending SMS directly to a lecturer, it might distract an ongoing class or meetings attended by the lecturer. Therefore, the objective of this project is to develop an instant way of tracking the availability of a lecturer in their room without having to disturb their privacy through the use of SMS technology and Java application system. Using a Java application system, lecturers can update their availability status at their room. The application is linked to the MySQL database server. An SMS server will be configured to receive SMS from a student and sending back the availability status of a lecturer to the student mobile phone. This creates an instant way of tracking the availability of the lecturers at their room using the technology of SMS and Java.